Resection of the Inferior Vena Cava Due to Tumor Involvement Allows Long-Term Survival in Different Neoplasms - Isabel Jaén-Torrejimeno; Diego López-Guerra; Adela Rojas-Holguín; Antonio Enrique Gómez-Martin; Gerardo Blanco-Fernández (Gastroenterology Insights)
Background: The involvement of the inferior vena cava in advanced abdominal tumors is a surgical challenge, given the high postoperative morbidity and poor long-term prognosis. Our goal was to analyze our experience, perioperative management, and results. Methods: We retrospectively evaluated short and long-term results of surgical resections of tumors with associated inferior vena cava resection performed in our facilities between 2012 and 2023. Results: A total of 25 patients were selected for our retrospective study: 3 with renal carcinoma, 5 with sarcoma, 12 with metastatic lesions, 2 with adrenal tumors, 1 pancreatic tumor, 1 extra-adrenal paraganglioma and 1 with hepatocellular carcinoma. Postoperative severe complications (Dindo-Clavien score ≥ IIIa) affected 36% of patients and the mortality rate was 8%. Partial resection with primary repair was performed in 13 patients (52%), with patch reconstruction in 6 (24%), and vascular reconstruction with prosthesis in 6 patients (24%). The mean disease-free survival was 7 months (IQR 2.5–11.5). Graft thrombosis occurred in 2 patients during follow-up. Conclusions: In selected patients, the resection of the inferior vena cava is a complex surgery with an assumable morbimortality and relative survival improvement.